الخرائط اللّسانية بين النظم والرقمنة - مسيلي, وردة; سراوي, سهام (جامعة الوادي - university of Eloued, 2021)
يهدف هذا البحث الموسوم "الخرائط اللسانية بين النظم والرقمنة" إلى التعرف على آليات رسم الخرائط الرقمية اللّسانية، محاولة الإجابة عن إشكال كيفية نظم الظواهر اللغوية واستقصاء التنوع اللهجي في المستوى الصوتي وتدوين مجسدتها في برامج التخريط الحاسوبي. وتتجلى أهمية هذا البحث في دور استخدام التكنولوجيا الرقمية في مجال الجغرافية اللغوية ورسم خرائط لسانية رقمية، لذلك كان البحث تطبيقيا مركزا على كيفية نظم الظواهر اللهجية متخذة لهجة ميلة -أنموذجا -للدراسة ورسم خريطة رقمية لها لظاهرة الإبدال الصوتي( حرف القاف). This map between systems and digitization amis to identify the mechanics of storing digital linguistic maps; try to answer to the problem how to organize linguistic phenomena; invitigate on the methodological diversity in the phonemic level and codify theirs empoduments in the computer mapping program. The importance of this research is in the use of digital technology in linguistic geography and drawing digital linguistic maps. Therefore this research was practical and focused on how we organize dialect phenomena-mila dialect as a model- for the study and draw a digital map to the voice substitution phenomena ( letter k)
مقال
Keywords: لسانيات جغرافية؛ خرائط رقمية؛ نظم؛ برامج؛ ظواهر لغوية